(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the role of the human factor in the media space in modern societies and states. The issues of the rapid development of Media and Technology, their impact on the structures of society and the state, how the human factor is formed in the media space and achieving efficiency through new approaches are studied. Also analyzed were information security problems and new approaches to solving them, special laws, regulations and international cooperation. The role of social media platforms in shaping public opinion and their monitoring and analysis approaches have been examined. Data on algorithms and control systems were collected to prevent misinformation from spreading. Approaches to the educational system for the development of media literacy, digital literacy courses and community campaigns were studied. The data found was analyzed and synthesized. The main problems and approaches in each direction were identified, and their significance and results were evaluated.